Mineral Composition of Cottonseed is Affected by Fertilization Management Practices. (1st March 2013) - He, Zhongqi; Shankle, Mark; Zhang, Hailin; Way, Thomas R.; Tewolde, Haile; Uchimiya, Minori
Abstract : Cottonseed and its products can be used as human food, animal feed, and industrial raw material. Chemical composition is one of the critical parameters to evaluate cottonseed's quality and potential end use. Whereas there are reports on the improvement of cotton ( Gossypium hirsutum L.) lint yield by poultry litter (PL) fertilization, there are no data about the impact of PL application on mineral composition of cottonseed. In this study, we collected seed samples in 2 yr from cotton fertilized with PL and chemical inorganic fertilizer (CIF) with or without winter wheat ( Triticum aestivum L.) cover crop (CC) at the Mississippi Agricultural and Forest Experiment Station. Contents of 18 elements (Al, As, B, C, Ca, Cd, Cu, Fe, K, Mg, Mn, N, Na, Ni, P, Pb, S, and Zn) and ash in these cottonseed samples were determined by inductively coupled plasma‐based or dry combustion methods. Cover crop did not significantly impact the chemical composition of cottonseed. Compared to no fertilizer control, both CIF and PL altered the levels of Ca, Mg, Cu, Fe, Mg, Mn, P (possibly Na and K), and ash contents but not C, N, Zn, Ni, Cd, Pb, Al, S, B and As. The impact of subsurface band vs. broadcast application methods or fall vs. spring application timing on mineral composition was not obvious. Cottonseed K, Mg, and P contents were higher with PL fertilization but lower with CIF than those of the control cottonseed (no fertilizer). The data of the three elements were highly correlated (α < 0.01), indicating the three elements were co‐accumulated in cottonseed.